Genera of phytopathogenic fungi: GOPHY 3 - Y. Marin-Felix (Studies in Mycology, 2019)
This paper represents the third contribution in the Genera of Phytopathogenic Fungi (GOPHY) series. The series provides morphological descriptions, information about the pathology, distribution, hosts and disease symptoms for the treated genera, as well as primary and secondary DNA barcodes for the currently accepted species included in these. This third paper in the GOPHY series treats 21 genera of phytopathogenic fungi and their relatives including: Allophoma, Alternaria, Brunneosphaerella, Elsinoe, Exserohilum, Neosetophoma, Neostagonospora, Nothophoma, Parastagonospora, Phaeosphaeriopsis, Pleiocarpon, Pyrenophora, Ramichloridium, Seifertia, Seiridium, Septoriella, Setophoma, Stagonosporopsis, Stemphylium, Tubakia and Zasmidium. This study includes three new genera, 42 new species, 23 new combinations, four new names, and three typifications of older names. Key words: DNA barcodes, Fungal systematics, New taxa, Taxonomic novelties: New genera: Arezzomyces Y. Marín & Crous, Globoramichloridium Y. Marín & Crous, Wingfieldomyces Y. Marín & Crous, New species: Allophoma pterospermicola Q. Chen & L. Cai, Alternaria aconidiophora Iturrieta-González, Dania García & Gené, Alternaria altcampina Iturrieta-González, Dania García & Gené, Alternaria chlamydosporifera Iturrieta-González, Dania García & Gené, Alternaria curvata Iturrieta-González, Dania García & Gené, Alternaria fimeti Iturrieta-González, Dania García & Gené, Alternaria inflata Iturrieta-González, Dania García & Gené, Alternaria lawrencei Iturrieta-González, Dania García & Gené, Alternaria montsantina Iturrieta-González, Dania García & Gené, Alternaria pobletensis Iturrieta-González, Dania García & Gené, Alternaria pseudoventricosa Iturrieta-González, Dania García & Gené, Brunneosphaerella roupeliae Crous, Elsinoe picconiae Crous, Elsinoe veronicae Crous, Thangavel & Y. Marín, Neosetophoma aseptata Crous, R.K. Schumach. & Y. Marín, Neosetophoma phragmitis Crous, R.K. Schumach. & Y. Marín, Neosetophoma sambuci Crous, R.K. Schumach. & Y. Marín, Neostagonospora sorghi Crous & Y. Marín, Parastagonospora novozelandica Crous, Thangavel & Y. Marín, Parastagonospora phragmitis Crous & Y. Marín, Phaeosphaeriopsis aloes Crous & Y. Marín, Phaeosphaeriopsis aloicola Crous & Y. Marín, Phaeosphaeriopsis grevilleae Crous & Y. Marín, Phaeosphaeriopsis pseudoagavacearum Crous & Y. Marín, Pleiocarpon livistonae Crous & Quaedvl., Pyrenophora avenicola Y. Marín & Crous, Pyrenophora cynosuri Y. Marín & Crous, Pyrenophora novozelandica Y. Marín & Crous, Pyrenophora pseudoerythrospila Y. Marín & Crous, Pyrenophora sieglingiae Y. Marín & Crous, Pyrenophora variabilis Hern.-Restr. & Y. Marín, Septoriella germanica Crous, R.K. Schumach. & Y. Marín, Septoriella hibernica Crous, Quaedvl. & Y. Marín, Septoriella hollandica Crous, Quaedvl. & Y. Marín, Septoriella pseudophragmitis Crous, Quaedvl. & Y. Marín, Setophoma brachypodii Crous, R.K. Schumach. & Y. Marín, Setophoma pseudosacchari Crous & Y. Marín, Stemphylium rombundicum Moslemi, Y.P. Tan & P.W.J. Taylor, Stemphylium truncatulae Moslemi, Y.P. Tan & P.W.J. Taylor, Stemphylium waikerieanum Moslemi, Jacq. Edwards & P.W.J Taylor, Vagicola arundinis Phukhams., Camporesi & K.D. Hyde, Zasmidium thailandicum Crous, New combinations: Arezzomyces cytisi (Wanas. et al.) Y. Marín & Crous, Globoramichloridium indicum (Subram.) Y. Marín & Crous, Phaeosphaeria phoenicicola (Crous & Thangavel) Y. Marín & Crous, Pyrenophora poae (Baudyš) Y. Marín & Crous, Pyrenophora wirreganensis (Wallwork et al.) Y. Marín & Crous, Seiridium cupressi (Nattrass et al.) Bonthond, Sandoval-Denis & Crous, Seiridium pezizoides (de Not.) Crous, Septoriella agrostina (Mapook et al.) Y. Marín & Crous, Septoriella artemisiae (Wanas. et al.) Y. Marín & Crous, Septoriella arundinicola (Wanas. et al.) Y. Marín & Crous, Septoriella arundinis (W.J. Li et al.) Y. Marín & Crous, Septoriella bromi (Wijayaw. et al.) Y. Marín & Crous, Septoriella dactylidis (Wanas. et al.) Y. Marín & Crous, Septoriella elongata (Wehm.) Y. Marín & Crous, Septoriella forlicesenica (Thambug. et al.) Y. Marín & Crous, Septoriella garethjonesii (Thambug. et al.) Y. Marín & Crous, Septoriella italica (Thambug. et al.) Y. Marín & Crous, Septoriella muriformis (Ariyaw. et al.) Y. Marín & Crous, Septoriella rosae (Mapook et al.) Y. Marín & Crous, Septoriella subcylindrospora (W.J. Li et al.) Y. Marín & Crous, Septoriella vagans (Niessl) Y. Marín & Crous, Wingfieldomyces cyperi (Crous & M.J. Wingf.) Y. Marín & Crous, Zasmidium ducassei (R.G. Shivas et al.) Y. Marín & Crous, New names: Pyrenophora nisikadoi Y. Marín & Crous, Septoriella dactylidicola Y. Marín & Crous, Septoriella neoarundinis Y. Marín & Crous, Septoriella neodactylidis Y. Marín & Crous, Typification: epitypification: Ascochyta chrysanthemi F. Stevens, Pestalotia unicornis Cooke & Ellis, Rhynchosphaeria cupressi Nattrass et al